2012
DOI: 10.1093/icvts/ivs255
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of carbon dioxide during endoscopic vein harvest

Abstract: There was a constant increase in the blood gas concentration compared with the basal pre-procedure values. Sealed systems were associated with a significantly higher CO(2) concentration at the end of the procedure compared with the open ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…With two articles identified by a manual search of references, finally, 40 articles from 34 RCTs were eligible for quantitative data syntheses. Two RCTs [28,29] which compared open EVH versus closed EVH were excluded from the main analysis. One RCT [23], which combined open EVH and closed EVH to compare with CVH, was excluded from the sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With two articles identified by a manual search of references, finally, 40 articles from 34 RCTs were eligible for quantitative data syntheses. Two RCTs [28,29] which compared open EVH versus closed EVH were excluded from the main analysis. One RCT [23], which combined open EVH and closed EVH to compare with CVH, was excluded from the sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
“…With two articles identified by a manual search of references, finally, 40 articles from 34 RCTs were eligible for quantitative data syntheses. Two RCTs[28,29] which compared open…”
mentioning
confidence: 99%
“…There are further concerns regarding the creation of a carbon dioxide tunnel around the harvest conduit [26][27][28] and our previous study has demonstrated that there was no impact by the tunnel 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypercarbia is also influenced by the tunnel pressure or the type of system being used for EVH. [ 4 5 ] Higher tunnel pressures and closed EVH systems (which were used in this case) are associated with a higher incidence of hypercarbia.…”
mentioning
confidence: 99%